Collection and installation technique and its role in the artist's experience Ai Weiwei (An analytical study) (Journal of the College of Basic Education, 2023)
Summary of the research:Our tagged research (collection and installation technique and its role in the artist Ai Weiwei's experience) deals with two main chapters: Chapter One: The general methodological framework that includes / the research problem and its importance: which lies in highlighting the impact of technical transformations in contemporary art formation, which constitute a significant shift on The level of paradigm shift in artistic and intellectual performance, which has now become a revealer of its importance in presenting the idea and preferring it over individuality, in innovation and innovation in creative artistic production and the mechanisms of its output, and this is what reinforced friction in various techniques and mechanisms of display. It is considered a transitional stage in the intellectual structure of many existing artistic trends. On the basis of the idea. Especially the uniqueness and distinction of the collection and installation technique and its impact on the transformation and development of postmodern art productions.., Let us come up with several questions for the problem: What is the technique of collection and installation and the mechanisms of showing it in contemporary art formation? What are the formal transformations that occurred through the artistic achievement? What is the role of the collection and installation technique in directing the artistic experience of the artist Ai Weiwei? And what are the means and mechanisms adopted by him in producing his artistic production through this technique?), passing through the aim of the research, which is to identify the collection and installation technique and its role in the artist Ai Weiwei’s experience. With fixing the spatial, temporal, and objective limits of our tagged research, with defining the terms involved in the collection and installation technique. As for the second chapter (theoretical framework), it included two sections: the first topic (collection and installation technique in artistic formation), which sheds light on the important role of the collection and installation technique in the development and change in the artist’s experiences towards the unfamiliar and shocking the recipient with exoticism and provoking controversy towards it, which led him towards a transformation in matter Experimentation with multiple materials and raw materials, especially towards the contrast and integration of painting and sculpture with other arts, and the promotion of mixed art based on the use of different materials used in artistic formation to put art on new frontiers of movements in various artistic output, especially postmodern arts. With the mention of its most important artists and their intentional experiences, who are considered the basis for activating the technique and reversing the previous standards through it, breaking the boundaries of the accomplished towards existence and coupling it with other artistic methods of unfamiliar and visually different artistic creation. As for the second topic: (collection and installation technique and its role in the art experience Ai Weiwei): in it we shed light on the uniqueness of the distinguished artist in his approach to the language of expression and its achievement through the concept of art as an idea and integrated with the technique of collection and installation in forming his strange and unfamiliar artistic productions, and its prominent role in expressing his subjects different formulations according to new formulations of the concept of idea and meaning, in his representation and immediate spatio-temporal recording of the event in reality, as a language of discourse with reception through which his messages directed towards the audience are conveyed, with a transfer from his conceptual and theoretical descriptions, to his holdings of sensory formal elements and vocabulary borrowed from his lived social environment, which turned into Practical propositions that represent composite formative features of the conceptual achievement. With the reinforcement of the most prominent artistic experiments accomplished by him through the technique of collection and installation. To the third chapter, the results and conclusions, some of which we review: (1. The artist Ai Weiwei is one of the artists who approached their language of expression and achieved it through the concept of art as an idea and activated by employing the technique of collection and installation in shaping his artistic productions, and its role in expressing his various subjects, establishing his artistic experience according to For new formulations of the concept of idea and meaning, in its representation and instantaneous recording of the event in reality 2. The clever employment of different or consumed materials and their conversion into an innovative artistic product of new non-stereotypical forms through the technique of collection and installation, illusion of sight with other composite materials in new unfamiliar forms. The technique and the mechanism of its work for the artist is an important factor in pushing him towards its confrontation with other arts such as the art of architecture and its merging with its huge walls.) As for the conclusions, some of them are: (1. The social, cultural and political environment was a major source of (inspiration and mental reflections) that helped him with new ideas, activated by his technique Contemporary, which reveals its influential role in producing those huge and strange sculptural edifices, which unite with its important small parts to form a whole, in line with the artist's view of the world that the part is no less important and unique than the whole. Expressing himself as an official discourse distinguished with reality and personal memory, sanctifies the individual in society by relying on his borrowed formal vocabulary and intentionally linked to the social environment and its cultural heritage. The natural and manufactured pension of various raw materials, which formed the language of an advertising discourse directed directly to the recipient, sends its influences on the mind of the recipient, to interact with him, to launch his intellectual readings towards it, and in turn announces that interactive process achieved between them, the game of vulnerability and communication or communication between them at the moment of the shock to the recipient.) . Mentioning some of the recommendations and proposals, some of which are: Recommendations: Develop curricula that highlight the importance and role of the collection and installation technique in the plastic arts. A proposal for a study in: the aesthetics of the visual presentation of the products of collection and installation in contemporary art formation). With the list of sources and references that we adopted in writing the research.Keywords: technology - collection - installation - collection and installation.